Surveying American Jews and their views on Middle East politics: The current situation and a proposal for a new approach - Joel Perlmann (Levy Economics Institute of Bard College, 2007)
This working paper takes up three related themes. In section 1, I briefly describe the issues relevant to surveying American Jews and highlight the importance of authoritative national surveys; in section 2, I note that these surveys have not included much exploration of American Jewish divisions over Israeli and American Middle East policy. In section 3, I propose the rudiments of a sample design that would meet the traditional needs of the national survey as well as the political opinion poll. This design is based on a rotating national panel of respondents, somewhat like the U.S. government's Current Population Survey. At the same time, data from earlier panels can be combined to increase sample size for the study of sociocultural issues that are less immediate in nature. Readers who are primarily interested in the issue of polling political opinion about Israeli and American Middle East policy may wish to read only sections 2 and 3. Those primarily interested in the proposal for a national survey based on a rotating panel may wish to read only section 3.
Keywords: 330